The Relationship Of Peer Social Support With The Learning Motivation Of Citizens Learning The Package C Program At PKBM Raudhatul Ullum Padang Pariaman District - Andriani, Desi; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The aim of this research is to find out whether social support from peers influences the motivation of students to study at PKBM Raudhatul Ullum. This research uses a correlational quantitative approach. The population of this study were students at PKBM Raudhatul Ullum. With a population of 92 people. The sampling technique in this research was carried out using a cluster random sampling technique. Therefore, the author took 45% of the population, so the sample size was 45% x 92 = 41 people. The data analysis technique used percentages to look for correlations using the product moment formula. The results of this research are: 1.) Social support from peers at PKBM Raudhatul Ullum is classified as less supportive. 2.) The learning motivation of students studying at PKBM Raudhatul Ullum is relatively low. And 3.) There is a significant relationship between learning motivation and social support from peers among residents studying Package C of the Equality Program at the Raudhatul Ullum Community Learning Activity Center (PKBM).Keywords: peer social support, learning motivation, package C.